APLIKASI INFORMASI UKM PADA UNIVERSITAS DI JAKARTA UTARA - Christianto, Kevin; Budiyantara, Agus; Lee, Francka Sakti; Andry, Johanes Fernandes; Bernanda, Devi Yurisca; Ananda, Deah (Infotech: Journal of Technology Information, 2025)
Limited access to information about Student Activity Unit (UKM) activities and achievements is often an obstacle for students, especially new students, to be actively involved in campus activities. This study aims to develop an UKM Information Application to provide an integrated platform that makes it easier for students at universities in North Jakarta to access UKM information. This application is designed using the Scrum method, with iterative stages that include user needs analysis, development of key features such as delivery of activity information, event notifications, and documentation of UKM achievements, and evaluation through sprint reviews. The use of this application is expected to increase information transparency, facilitate communication between members, and encourage student participation in UKM activities. The results of the study are in the form of a digital-based information application that can strengthen UKM management and communication effectively and efficiently, supporting the modernization of information systems in higher education.